2006
DOI: 10.1002/chem.200501548
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Electron Transfer in α‐Cyclodextrin‐Based Supramolecular Dyads: A Free‐Energy‐Dependence Study

Abstract: Photoinduced electron transfer (PET) between alpha-cyclodextrin-appended pyrene (PYCD) and a few acceptor molecules was studied in aqueous solutions. The pyrene moiety in PYCD is located above the narrower rim of the alpha-CD and is fully exposed to water. The acceptors are monocyclic organic molecules and, upon dissolution in water in the presence of PYCD, a fraction of the donor-acceptor systems is present as supramolecular dyads and the remaining fraction as free molecules. Free-energy-dependence studies sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 78 publications
3
8
0
Order By: Relevance
“…Photoexcitation of the system would then lead to unimolecular and bimolecular electron-transfer processes, as demonstrated previously for a-CD-appended systems [4] and hydrogenbonded systems. [18] An important difference in the present study is that the triplet excited state of the AN chromophore is also involved in the electron-transfer process.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…Photoexcitation of the system would then lead to unimolecular and bimolecular electron-transfer processes, as demonstrated previously for a-CD-appended systems [4] and hydrogenbonded systems. [18] An important difference in the present study is that the triplet excited state of the AN chromophore is also involved in the electron-transfer process.…”
mentioning
confidence: 88%
“…[4] The acceptors were monocyclic aromatic molecules capable of encapsulation in the a-CD cavity. PET processes in these dyads were probed by fluorescence lifetime quenching experiments, which showed that PET reactions in the CD-based dyad systems obey the Marcus equation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As per the scheme both static and dynamic quenching pathways exist and this leads to the observed bi-exponential decay profiles. 8,30,31,35,61 The bi-exponential profiles were fitted using equation 3 to obtain lifetimes τ 1 and τ 2 and their respective contributions χ 1 and χ 2 .…”
Section: Time-resolved Fluorescence Experimentsmentioning
confidence: 99%
“…Cyclodextrins (CDs), which are cyclic oligosaccharides with hydrophobic cavities, are ideal molecular receptors for building water-soluble supramolecular functional assemblies. [15][16][17][18][19] Recently others [20][21][22][23][24][25][26][27][28][29] and we 30,31 have employed chromophore-appended CDs to assemble supramolecular D-A systems for PET reactions in water. The hydrophobic nature of the CD cavity acts as the assembler of the D-A system here.…”
Section: Introductionmentioning
confidence: 99%